Factors Influencing the Adoption of Digital Waste Banks: A Systematic Literature Review - Nur Isni Nirwan; Dana Indra Sensuse (Scientific Journal of Informatics, 2026)
Purpose: This study aims to identify and analyze the factors influencing the adoption of digital waste banks, considering the gap between their potential to improve waste management and their limited implementation in many regions. Methods/Study design/approach: This research use a Systematic Literature Review (SLR) approach by analyzing 22 selected studies published between 2020 and 2025 from reputable databases. The study follows structured stages, including planning, literature selection based on inclusion and exclusion criteria, quality assessment, data extraction, and data synthesis using the PICOC framework. Result/Findings: The results show that there are 26 factors influencing the adoption of digital waste banks, which are grouped into four main categories: technology, organization, environment, and people. Technological factors include ease of use, transparency, system quality, and security. Organizational factors involve infrastructure, innovation, and human resources. Environmental factors include regulations, social influence, environmental awareness, and economic incentives. Meanwhile, people-related factors include age, education, income, and training. These factors are interconnected and play an important role in determining adoption success. Novelty/Originality/Value: This study provides a comprehensive classification of factors influencing digital waste bank adoption based on recent literature. The findings offer practical insights for policymakers and practitioners in designing strategies to increase community participation and improve sustainable waste management through digital innovation.